A complete guide to quality in small-scale wine making - Considine, John Anthony (Elsevier Science, 2013)
As the wine industry has experienced a period of rapid global expansion, there is a renewed emphasis on quality and consistency even within the small winery industry. Written for the small production program, A Complete Guide to Quality in Small-Scale Wine Making is for the novice to intermediate level winemaker seeking foundational information in chemistry and sensory science as they relate to wine quality at a technical level. Drawing from personal experience as well as scientific literature, this book introduces the core concepts of winemaking before delving into me.